Effect of tectonic coal structure on methane adsorption. Issue 6 (December 2021) - Yang, Hong; Bi, Wenyan; Zhang, Yugui; Yu, Jikong; Yan, Jiangwei; Lei, Dongji; Ma, Zhangnan
Abstract: The research of methane adsorption in coal is of great significant for controlling methane emission and reducing the greenhouse gas. The Fourier Infrared Spectrum experiments, isothermal adsorption experiments and methane adsorption experiments were conducted to study the effect of tectonic coal structure on methane adsorption from the different of tectonic coal and raw coal, the solvent extraction role, the chemical component and the pore structure. The extraction yield order of different metamorphic degrees tectonic coals by pyridine was as follows: tectonic fat coal (31.14%) > tectonic gas coal (18.42%) > tectonic anthracite coal (0.24%), which indicated the content of small molecules. The methane ultimate adsorption amount had relation with the ratio of -CHx functional groups to oxygen functional groups. The order of micropore volume was tectonic anthracite coal (44.07 × 10 −3 cm 3 g −1 ) > tectonic fat coal (13.67 × 10 −3 cm 3 g −1 ) > tectonic gas coal (13.60 × 10 −3 cm 3 g −1 ). Methane adsorption was mainly micropore adsorption, functional groups in coal affected available adsorptive positions, and the low molecular compounds in coal affected its adsorption capacity. The tectonic coal with high metamorphic degree, such as tectonic anthracite coal, has a very high adsorption capacity for methane and has a good prospect in controlling methane emission and reducing greenhouse gas. Graphical Abstract: ga1 Highlights: Study methane treatment method through the relationship between tectonic coal structure and methane adsorption. The existence of low molecular compounds in coal restricts the adsorption capacity of methane. The ultimate adsorption amount of methane in coal has relation with the ratio of functional groups . The methane adsorption capacity of tectonic coal is jointly controlled by the pore structure and molecular structure.